Quinoa flour, the germinated grain flour, and sourdough as alternative sources for gluten-free bread formulation: impact on chemical, textural and sensorial characteristics - Franco, Wendy (2021)
The demand for gluten-free breads has increased in the last years, but important qualityand nutritional challenges remain unsolved. This research evaluated the addition of quinoa in wholequinoa grain flour, germinated quinoa flour, and quinoa sourdough, as a functional ingredient in theformulation of a rice flour-based bread. Twenty percent (w/w) of the rice flour was replaced withquinoa flour alternatives in bread formulations. The chemical composition, shelf-life, and sensoryattributes of the rice-quinoa breads were analyzed. The addition of quinoa in sourdough resultedin breads with a significantly improved protein content at 9.82%, relative to 2.70% in the controlbreads. The amino acid content in quinoa sourdough breads also was also 5.2, 4.4, 2.6, 3.0, and2.1 times higher in arginine, glutamic acid, leucine, lysine, and phenylalanine, respectively, relativeto control breads with rice flour only. The addition of quinoa sourdough in rice breads also improvedthe texture, color, and shelf-life (up to 6 days), and thus they became moderately accepted amongconsumers. Although the germinated quinoa flour addition also resulted in a higher protein (9.77%)and amino acid content, they had a reduced shelf-life (4 days). Similarly, the addition of quinoa flourresulted in a higher protein content (9.61%), but the breads had poor texture attributes and were theleast preferred by the consumers.